2021
DOI: 10.1051/0004-6361/202040125
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition of comet 46P/Wirtanen from millimetre-wave spectroscopy

Abstract: We present the results of a molecular survey of comet 46P/Wirtanen undertaken with the IRAM 30-m and NOEMA radio telescopes in December 2018. Observations at IRAM 30-m during the 12–18 December period comprise a 2 mm spectral survey covering 25 GHz and a 1 mm survey covering 62 GHz. The gas outflow velocity and kinetic temperature have been accurately constrained by the observations. We derive abundances of 11 molecules, some being identified remotely for the first time in a Jupiter-family comet, including com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
52
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 52 publications
14
52
7
Order By: Relevance
“…Comet 21P is also depleted in NH (A'Hearn et al 1995) and NH 2 (Fink 2009) but showed unidentified emission near 8, 9 and 11 µm, some of which could be attributed to complex organics Ootsubo et al (2020). Unfortunately the sensitivity of the 2018 observations was limited and our upper limits on the abundance of complex organics such as NH 2 CHO or CH 3 CHO are higher than values measured in comets (Biver et al 2021), but nevertheless show that comet 21P is not strongly enriched (by a factor >5) in these molecules. The depletion of sulphur species, carbon-chain organics and NH 2 might be present in the volatile phase of comet 21P, but compensated by an enrichment in heavier refractory species as suggested by Ootsubo et al (2020).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Comet 21P is also depleted in NH (A'Hearn et al 1995) and NH 2 (Fink 2009) but showed unidentified emission near 8, 9 and 11 µm, some of which could be attributed to complex organics Ootsubo et al (2020). Unfortunately the sensitivity of the 2018 observations was limited and our upper limits on the abundance of complex organics such as NH 2 CHO or CH 3 CHO are higher than values measured in comets (Biver et al 2021), but nevertheless show that comet 21P is not strongly enriched (by a factor >5) in these molecules. The depletion of sulphur species, carbon-chain organics and NH 2 might be present in the volatile phase of comet 21P, but compensated by an enrichment in heavier refractory species as suggested by Ootsubo et al (2020).…”
Section: Discussioncontrasting
confidence: 53%
“…Line intensities have been converted to production rates using our time-dependent non-LTE code taking into account collisions with neutrals and electrons as well as solar radiative pumping via vibrational bands for HCN, CH 3 OH, CS, H 2 CO, CO, and CH 3 CN, as used in previous papers (Biver et al 2000(Biver et al , 2006(Biver et al , 2012(Biver et al , 2014(Biver et al , 2015(Biver et al , 2016. Photolysis constants are also from previous papers and detailed in Biver et al (2021). Production rates or upper limits are provided in Table 4.…”
Section: Production Rates and Abundancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Single dish observations are indicated with striped bars. Column densities taken from the literature 9,10,12,13,15,16,19,20,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] are presented in Table S3 in the supporting information.…”
Section: Discussionmentioning
confidence: 99%
“…Formamide (NH 2 CHO) has the same chemical structure as a peptide bond and is the simplest peptide-like molecule. It is the first peptide-like molecule to be detected in the interstellar medium (ISM) and is routinely found in extraterrestrial environments, ranging from star-forming regions to comets [8][9][10] . Since the detection of formamide, several other peptide-like molecules have been detected, such as acetamide (CH 3 C(O)NH 2 ) 11 , N-methylformamide (CH 3 NHCHO) [12][13][14][15] , and urea (also known as carbamide, NH 2 C(O)NH 2 ) 13,16 .…”
Section: Introductionmentioning
confidence: 99%